Jurassic–Early Cenozoic Tectonic Inversion in the Qilian Shan and Qaidam Basin, North Tibet: New Insight From Seismic Reflection, Isopach Mapping, and Drill Core Data. Issue 11 (19th November 2019) - Cheng, Feng; Jolivet, Marc; Guo, Zhaojie; Lu, Huayu; Zhang, Bo; Li, Xiangzhong; Zhang, Daowei; Zhang, Changhao; Zhang, Hanzhi; Wang, Lin; Wang, Zhenqiang; Zhang, Qiquan
Abstract: The pre‐Cenozoic structural pattern of Asia has had a strong impact on the localization and propagation of the Cenozoic deformation that gave birth to the Tibetan Plateau. Northern Tibet represents a key area to decipher the structural and kinematic links between the Mesozoic and Cenozoic evolution of Tibet. Nonetheless, the Mesozoic tectonic setting of the North Tibet and the role that the Paleozoic inherited Altyn Tagh Fault (ATF) shearing zone played in controlling the regional tectonic pattern during the deposition of the Mesozoic strata remain controversial. This study is based on seismic reflections, isopach maps of the Mesozoic strata in the Qaidam Basin, and provenance analysis using detrital zircon geochronological and heavy mineral contents. Seismic reflections and isopach maps demonstrate that sustained strike‐slip motion along the ATF during the Early to Late Jurassic induced transtensional basin formation. Further away from the main ATF (eastern parts of the Qilian Shan and the northern Qaidam Basin), transtension also occurred along major faults, although local transpression developed in relay zones. Rotation in the regional stress field induced compression and basin inversion during the Late Jurassic to Early Cretaceous. The Cenozoic sedimentary rocks in these regions display widespread growth strata and angular unconformities characteristic of compression. This is consistent with topographic changes marked by sediment source variation evidenced by detrital zircon geochronology and heavy mineral analysis. We propose that the mechanism driving the Jurassic extension/transtension in North Tibet could be related to far‐field effects of subduction processes along the southern margins of the continent. Key Points: Mesozoic strike‐slip motion along the Altyn Tagh Fault (ATF) shearing zone controlled the formation of transtensional basins Change in the direction of regional stress field occurred during the Late Jurassic‐Early Cretaceous The Qilian Shan and the Qaidam Basin were completely inverted under a N‐S or NE‐SW oriented compression during the Early Cenozoic